Cristiano Pintaldi - Codognato, Mario; D'Orazio, Costantino; Maraniello, Gianfranco; Pintaldi, Cristiano; Pratesi, Ludovico; Scarpa, Tiziano; Stella, Giuliana; Centro per le Arti Visive Pescheria Pesaro (Milano : Edizioni Charta Milano, 2002)
The works of Cristiano Pintaldi confront the powerful, persuasive images of the mass media. Like the television screen, which on close inspection simply relays sequences of colored dots (pixels), Pintaldi's paintings are alchemies of color in which the tonalities of red, green and blue, on a black canvas, construct images recognizable only from a certain distance. The subjects seem to reflect this perspective, too, through references to realities that are not part of ordinary experience : aliens, which are the focus of an extensive series, Pygmies, lightning, the Twin Towers terrorist attack and Big Brother, all of which fascinate the artist with their varied nature as planetary Media Events. One of the youngest artists represented in the permanent collection of the Galleria Nazionale d'Arte Moderna in Rome, Pintaldi was a prize-winner at the Quadriennale d'Arte in 1996. This book is a kind of diary of the aritst, containing his notes, his words and the comments of his fellow artists over the last ten years.
Cristiano Pintaldi, Centro per le Arti Visive Pescheria Pesaro, 2 giugno - 7 luglio 2002
biog., ind. tent., gr. tent., prijzen p. 61-62, bibliog. p. 63
Engels
Italiaans
boek
Keywords: Pintaldi, Cristiano